The effect of macro economy, liquidity, and profitability on investment risk in companies listed on the Jakarta Islamic Index (JII) - Malia Anggrainy (The Indonesian Accounting Review, 2015)
The economic crisis in Indonesia had an impact on the declining performance of the company’s fundamental in the stock market. Investment is the placement of funds at this time for making a profit in the future. Investment is always associated with return and risk. Investors are willing to accept greater risks but should also be compensated by the opportunity to get greater return. This research aims to find the effect of infla-tion, interest rate, and the exchange rate that represent the macro-factors and the level of liquidity and profitability (ROA) of the company that represent micro-factors ont the risk of stocks investment in companies listed on the Jakarta Islamic Index (JII). The sample used is 13 companies using purposive sampling techniques. The statistical analysis of this research is done by using multiple regression analysis. The results show that inflation rate, exchange rate, and liquidity do not have significant effect on investment risk, while interest rate and profitability have significant effect on invest-ment risk.